Advanced materials : proceedings of the International Conference on "Physics and Mechanics of New Materials and Their Applications", PHENMA 2017 /: proceedings of the International Conference on "Physics and Mechanics of New Materials and Their Applications", PHENMA 2017. (2018) - Unknown
No abstract available